High current density, low threshold field emission from functionalized carbon nanotube bucky paper - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Late, Dattatray J.; Chavan, Padmakar G.; Sheini, Farid J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2010)
Field emission studies of bucky paper of multiwalled carbon nanotubes (MWNTs), prepared after microwave (MW) assisted acid functionalization are reported along with a comparison with that of ``as-grown'' sample. MW treated bucky papers reveal an interesting linear field emission behavior in Fowler-Nordheim plot. The field emission currents at preset value are found to be remarkably stable over a period of more than 3 h sustaining current densities of 4.9 mA/cm(2) and 8.5 mA/cm(2) for ``as-grown'' and functionalized sample, respectively. The enhancement in the field emission due to functionalization has been discussed in terms of tip opening and defect induced charge transport caused by intershell and intertubular interaction. (C) 2010 American Institute of Physics. [doi:10.1063/1.3479049]
Keywords: Carbon nanotubes; current density; field emission; fullerenes

Synthesis of single crystalline CdS nanocombs and their application in photo-sensitive field emission switches - Chavan, Padmakar G.; Badadhe, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Nanoscale, 2011)
Single crystalline CdS nanocombs were synthesized by a thermal evaporation route. The photo-sensitive field emission current shows a reproducible switching behavior, with a rise in current level of nearly five times the initial preset value of similar to 1 mu A. An ultra low turn-on field, required to draw an emission current density of similar to 0.1 mu A cm(-2) (100 nA), is found to be similar to 0.26 V mu m(-1) (260 V), which is much lower than the reported values for various other CdS nanostructures. Upon illumination with visible light the CdS nanocombs act as a photo field emission switch. At an applied field of similar to 0.65 V mu m(-1) the current densities are observed to be similar to 14.6 mu A cm(-2) and similar to 26.9 mu A cm(-2), without and with light illumination, respectively. The average emission current is seen to be stable over the duration of measurement for two preset values. The high sensitivity and fast response in the visible range indicates that the CdS nanocombs can be used as a photo-sensitive field emitting switch in device applications, and also in pulsed electron beam technology.

CdS nanowires: ultra-long growth and enhanced field emission properties - Chavan, Padmakar G.; Kashid, Ranjit V.; Badhade, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Vaccum, 2014)
Here, we report the synthesis of ultra-long CdS nanowires with aspect ratio similar to 8 x 10(4) by simple route of thermal evaporation technique. A change in the vertical arrangement of quartz boats leads in to the synthesis of ultra-long CdS nanovvires via high degree of condensation. This technique is seen to be cost effective and easy. The growth of the nanowires is found to be increased very rapidly from few micrometers to few millimeters. The possible reason for the growth of the ultra-long CdS nanowires is discussed in detail. The turn-on field defined for the current density of similar to 0.1 mu A/cm(2) has been found to be similar to 1.4, 1.45, 1 and 0.17 V/mu m for specimen A, B, C and D (specimens A-D, synthesized by variation in synthesis parameters) respectively. The turn-on field of the specimen D (similar to 0.17 V/mu m) is found to be quite superior than the value reported for other CdS nanoforms which is very remarkable. Simple way of bulk fabrication leads to the low turn-on value which indicates a possible use of the present emitter in the micro/nanoelectronics devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current stability; field emission; synthesis

Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Low turn-on field and high field emission current density from Ag/TiO 2 nanocomposite - Patil, Girish P.; Deore, Amol B.; Bagal, Vivekanand S.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Chemical Physics Letters, 2016)
High current density of 1.24 mA/cm2 was drawn at an applied field of 4.4 V/μm from Ag/TiO2 nanocomposite. Also the turn-on field has been reduced from 3.9 V/μm to 2.7 V/μm for the emission current density of 10 μA/cm2. Ag/TiO2 nanocomposite was synthesized by using UV-switchable reducing agent. TiO2 nanotube wall was decorated by Ag nanoparticles with average diameter of 17 nm. To the best of our knowledge this is the first report on the field emission studies of Ag/TiO2 nanocomposite. Simple synthesis route coupled with superior field emission properties indicate the possible use of Ag/TiO2 nanocomposite for micro/nanoelectronic devices.

Observation of enhanced field emission properties of Au/TiO2 nanocomposite - Patil, Girish P.; Bagal, Vivekanand S.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Applied Physics A-Materials Science & Processing, 2016)
Simple and low-cost method of thermal annealing was used to decorate Gold (Au) nanoparticles on aligned TiO2 nanotubes. The aligned TiO2 nanotubes were decorated by Au nanoparticles with an average diameter of 9, 18 and 28 nm (aligned TiO2 nanotubes referred as specimen A and TiO2 nanotubes decorated by Au nanoparticles with average diameter of 9, 18 and 28 nm are referred as specimen B, C and D, respectively). The detailed characterization such as structural, morphological and elemental analysis of TiO2 and Au/TiO2 nanocomposite have been carried out using X-ray diffraction, field emission scanning electron microscope, transmission electron microscope, X-ray photoelectron spectroscopy and Raman spectroscopy. Furthermore, the meticulous comparative field emission characteristics of the aligned TiO2 nanotubes and Au/TiO2 nanocomposite have been performed. The turn-on field defined for the current density of 10 mu A/cm(2) has been found to be 3.9, 2.8, 3.2 and 3.7 V/mu m for specimen A, B, C and D, respectively. The observed low turn-on field of specimen B has been found to be superior than the other semiconducting nanocomposites reported in the literature. The emission current stability over a period of 3 h is found to be better for all the specimens. To the best of our knowledge, a systematic field emission study of Au/TiO2 nanocomposite has not been explored. The observed superior field emission study of Au/TiO2 nanocomposite indicates their possible use in micro/nanoelectronic devices.

Surface modification of aligned CdO nanosheets and their enhanced field emission properties - Bagal, Vivekanand S.; Patil, Girish P.; Deore, Amol B.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (RSC Advances, 2016)
Porous aligned CdO nanosheets were grown on a cadmium (Cd) substrate by the simple and cost effective method of thermal annealing. Further, decoration of gold (Au) nanoparticles on the porous aligned CdO nanosheets (specimen A) was achieved by coating with a Au thin film and subsequent annealing treatment. The average diameters of decorated Au nanoparticles were found to be 15 nm, 21 nm and 28 nm for the Au thin films with 20 s, 40 s and 60 s (specimens B, C, and D) coating times. Detailed characterizations, such as structural and morphological analysis of porous CdO nanosheets and Au/CdO nanocomposite (Au decorated porous CdO nanosheets), have been carried out using a Field Emission Scanning Electron Microscope (FESEM), X-ray diffraction (XRD) and a Transmission Electron Microscope (TEM). Field emission studies of specimens A, B, C and D were carried out in the planar diode configuration. Turn-on fields of 1.9 V mu m(-1), 1.1 V mu m(-1), 2.4 V mu m(-1) and 2.8 V mu m(-1) have been found for the emission current density of 10 RA cm(-2) for specimens A, B, C and D, respectively. The observed low turn -on field of specimen B (Au diameter of 15 nm) was found to be superior to other semiconducting nanostructures reported in the literature. The field emission current stability over a period of 3 h at the preset current density of 1 RA cm(-2) is found to be excellent for all specimens. To the best of our knowledge, field emission studies along with surface modification of porous aligned CdO nanosheets have not been reported in the literature. The simple synthesis route, facile surface modification and the superior field emission results make the present emitter very suitable for micro/nano electronic devices.

Uncovering the origin of enhanced field emission properties of rGO-MnO(2)heterostructures: a synergistic experimental and computational investigation - Rondiya, Sachin R.; Karbhal, Indrapal; Jadhav, Chandradip D.; Nasane, Mamta P.; Davies, Thomas E.; Shelke, V. Manjusha; Jadkar, Sandesh R.; Chavan, Padmakar G.; Dzade, Nelson Y. (RSC Advances, 2020)
The unique structural merits of heterostructured nanomaterials including the electronic interaction, interfacial bonding and synergistic effects make them attractive for fabricating highly efficient optoelectronic devices. Herein, we report the synthesis of MnO(2)nanorods and a rGO/MnO(2)nano-heterostructure using low-cost hydrothermal and modified Hummers' methods, respectively. Detailed characterization and confirmation of the structural and morphological properties are doneviaX-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Compared to the isolated MnO(2)nanorods, the rGO/MnO(2)nano-heterostructure exhibits impressive field emission (FE) performance in terms of the low turn-on field of 1.4 V mu m(-1)for an emission current density of 10 mu A cm(-2)and a high current density of 600 mu A cm(-2)at a relatively very low applied electric field of 3.1 V mu m(-1). The isolated MnO(2)nanorods display a high turn-on field of 7.1 for an emission current density of 10 mu A cm(-2)and a low current density of 221 mu A cm(-2)at an applied field of 8.1 V mu m(-1). Besides the superior FE characteristics of the rGO/MnO(2)nano-heterostructure, the emission current remains quite stable over the continuous 2 h period of measurement. The improvement of the FE characteristics of the rGO/MnO(2)nano-heterostructure can be ascribed to the nanometric features and the lower work function (6.01 and 6.12 eV for the rGO with 8% and 16% oxygen content) compared to the isolated alpha-MnO2(100) surface (phi= 7.22 eV) as predicted from complementary first-principles electronic structure calculations based on density functional theory (DFT) methods. These results suggest that an appropriate coupling of rGO with MnO(2)nanorods would have a synergistic effect of lowering the electronic work function, resulting in a beneficial tuning of the FE characteristics.